CURRENT VIEWS ON THE INCIDENCE OF CONGENITAL SPINAL HERNIAS (World Bulletin of Public Health, 2024)
Modern medicine solves many problems related to the health of children, while prevention of perinatal and congenital pathologies is of great importance, the main focus of which is the health of the mother before and at the time of pregnancy
Keywords: congenital malformations; newborns; pregnancy